Reverse periodization in ultratrail: The road to the 2023 World Mountain and Trail Running Championships of an elite female ultrarunner - Diego Jaén-Carrillo; Arcadi Margarit-Boscà (Current Issues in Sport Science)
Introduction and Purpose